(untitled) (Cardiovascular Journal, 2022)
Background: Serum creatinine and blood urea nitrogen (BUN) are the common markers of renal function and also one of the known predictors of adverse outcomes of acute coronary syndrome (ACS). The aim of this study is to assess the impact of elevated BUN on in-hospital outcome of ACS patients and superiority of BUN over creatinine for the assessment of in-hospital outcome in our setting. Methods: This prospective observational study with purposive sampling of a total of 184 patients was conducted from October, 2009 to September, 2010. Based on normal cut off values (BUN and serum creatinine was <20 mg/dl and <1.4 mg/dl respectively) all the patients were divided into four groups; group I- both BUN and serum creatinine are normal, group-II- normal BUN and high serum creatinine, group-III- high BUN and normal serum creatinine, group-IV- - both BUN and serum creatinine are high. In-hospital data like hemodynamic conditions, heart failure, arrhythmias, conduction abnormalities, death etc. were noted. Assessment of in-hospital outcome of ACS patients and comparison to elevated serum creatinine and elevated BUN was done. Results: ACS patients with only raised BUN level had more occurrence of cardiogenic shock (p=0.008), left ventricular failure (p=0.020), ventricular Tachycardia (p=0.022), ventricular fibrillation (P=0.037) and complete AV block (p=0.022) than those with only raised serum creatinine. In hospital mortality and hospital stay was also increased in ACS patients with elevated BUN than elevated serum creatinine (p value is 0.022 and 0.007 respectively). Conclusion: Incidence of in-hospital death, cardiogenic shock, left ventricular failure, arrhythmia and duration of hospital stay were significantly (p<0.05) higher in patients who had raised BUN than raised serum creatinine. It is observed that elevated BUN is a better predictor of in-hospital outcome of ACS patients than elevated creatinine. Cardiovasc j 2022; 14(2): 135-142